E2FBP1/DRIL1, an AT-Rich interaction domain-family transcription factor, is regulated by p53 - Ma, Kaiwen; Araki, Keigo; Arief Ichwan, Solachuddin Jauhari (American Association for Cancer Research, 2003)
E2FBP1/DRIL1 is an AT-rich interaction domain DNAbinding protein and is ubiquitously expressed in various tissues. It has been shown that Bright, the mouse orthologue of E2FBP1/DRIL1, exhibits sequence-specific DNA binding and regulates immunoglobulin transcription. Here we show a novel connection between E2FBP1/ DRIL1 and the p53 tumor suppressor, a key regulator of growth arrest or apoptosis in response to cellular stress. We found a putative p53-binding site, which specifically responded to p53, in the second intron of the E2FBP1/ DRIL1 gene. E2FBP1/DRIL1was induced by p53 and upregulated following DNA damage caused by UV radiation or doxorubicin treatment in a manner dependent on endogenous p53. The ectopic expression of E2FBP1/ DRIL1 induced growth arrest in U2OS cells expressing normal p53, but not Saos-2 cells lacking p53. These results suggest that E2FBP1/DRIL1 may play a role in growth suppression mediated by p53.